Identifying Future Hydrographic Survey Priorities: A Quantitative Uncertainty Based Approach - Bongiovanni, Cassandra; Lippmann, Tom C.; Calder, Brian; Armstrong, Andrew (The International Hydrographic Review, 2021)
There is no universal standard methodology for assessing the validity of hydrographic survey data and charted information as they age. NOAA’s current method is the Hydrographic Health Model (HHM), a risk-based approach that incorporates crucial maritime variables and heuristic changeability terms through the history and frequency of large storms, tidal currents, and anthropogenic obstructions of a given area. Here we propose a quantitative approach evaluated in Chesapeake Bay and the Delmarva Peninsula that supports uncertainty-based estimates of chart health through alternative methodologies of calculating the initial state of historic hydrographic data and modeling how those change through time.